Unlocking rural resilience: Exploring innovative digital saving solutions for farming households in Mali - Annkathrin Wahbi; Oliver Musshoff (Journal of Agricultural Economics, 2024)
Financial savings at the household level are vital for poverty alleviation, yet they face social, psychological and institutional obstacles. Over recent years, mobile phones have proven effective in enhancing financial inclusion. However, when individuals decide how to save, their preferences remain unclear. This study investigates the preferences of 421 Malian smallholder farmers for a hypothetical mobile savings application using a discrete choice experiment. Apart from standard savings account features such as transaction charges, interest amount and minimum deposit requirements, it assesses preferences for two innovative features designed to address deviations from rational decision-making. The first feature allows multiple users to pool their savings, utilising social dynamics and peer pressure to encourage responsible savings behaviour and enhance commitment. The second feature offers users the ability to manage their finances more effectively by dividing them into purpose-specific sub-accounts. The findings reveal a strong overall preference for saving via the application rather than keeping cash on hand. As anticipated, farmers favour lower costs and deposits and higher interest amounts. Generally, individual saving is preferred over group saving, and the option to compartmentalise is valued, albeit not statistically significantly so. However, the analysis of underlying heterogeneity reveals substantial differences in respondents' preferences for these commitment-enhancing features. These findings underscore the need for customised approaches that align with farmers' unique preferences and constraints. Such approaches can inform the development of bespoke mobile savings solutions for farming households, thereby boosting their resilience and financial well-being.
Keywords: 630; behavioral economics; discrete choice experiment; financial planning; household finance; Mali; saving